The Effects of Geopolitical Risk on Korea’s Financial Market: Evidence from North Korea, the United States, and Japan - Hwang, Sunjae (Technium Social Sciences Journal, 2025)
This research examines South Korean financial market reactions to geopolitical risks through KOSPI index data and KRW/USD exchange rate movements during three significant events: North Korean nuclear tests and U.S.–China trade conflicts and Korea–Japan diplomatic tensions. The Event Study method revealed immediate market responses to North Korean military provocations which lost their effectiveness yet the U.S.–China trade conflict produced abnormal market volatility and Japan's export restrictions caused market responses that exceeded political tensions alone. The research presents different methods which organizations can use to build their resistance. The country of Singapore protected itself from risks through its diversified trade network and financial protection systems while Taiwan built stronger supply chain security and developed new international alliances and Israel used innovation to drive economic expansion while dealing with ongoing security challenges. The research findings provide essential knowledge for Korea to build stronger financial stability. The research demonstrates how geopolitical risks impact financial markets while showing that short-term stabilizing actions need to combine with enduring institutional changes to build market stability and global trust.